Telemedicine Platforms For Remote Healthcare Services (International Journal of Environmental Sciences, 2025)
By eliminating the need for in-person visits, telemedicine provides a practical and affordable alternative, particularly for remote locations. During the Covid-19 pandemic, this strategy was very helpful in enabling patients to obtain medical care while reducing travel and physical contact. Thus, telemedicine saves time and money for both the patient and the healthcare professional. In addition, because of its quick and beneficial nature, it is able to make the workflow of clinics and hospitals smoother. Such a cutting-edge technology could simplify the supervision of patients who have been discharged and their rehabilitation. The potential of telemedicine, treatment workflow features, and acceptance issues in the healthcare industry are examined in this study, emphasizing how it can benefit both patients and healthcare professionals. The study identifies seventeen noteworthy applications of telemedicine in the medical field. The ability of a doctor to treat and diagnose patients in a remote area is known as telemedicine. Using health applications to arrange follow-up visits increases efficiency for both patients and doctors, increases the likelihood of follow-up, reduces missed visits, and improves patient outcomes. In order to facilitate efficient remote diagnosis and treatment, patients should present a comprehensive medical history during telemedicine consultations and make use of top-notch audio-video technology to visually illustrate symptoms such as rashes, bruises, or other issues. Practitioners also need a payment gateway mechanism and file management. Both patients and physicians can go through the treatment procedure thanks to telemedicine technologies. However, this technology is not a substitute for a physical consultation; rather, it complements it. These days, especially during a pandemic, this technology offers patients who are unable to visit the hospital or remain at home a risk-free alternative.